2021
DOI: 10.1111/tan.14179
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic hematopoietic stem cell transplant recipients in Spain: Human leukocyte antigen characteristics and diversity by high‐resolution analysis

Abstract: There are many studies on the polymorphism of the HLA system in healthy donor populations, such as registries of unrelated bone marrow donors. Investigations on the characterization of the HLA complex in hematopoietic stem cell transplant (HSCT) patients, however, are scarce, at least in the Spanish population. This study presents a large‐scale analysis of allelic diversity and HLA distribution at a high‐resolution level in 2886 patients undergoing HSCT in Spanish centres of the “Grupo Español de Trasplante He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…An analysis of patients with rare HLA alleles (frequency <0.1) or HLA alleles which were not observed in our unpublished population data ( N = 10,000 from CBMDR), such as the HLA‐B*15:35, B*51:08, DRB1*11:15 , or DQB1*02:81 alleles, showed that those alleles which were part of a conserved HLA‐A~B~C~DRB1 haplotype were not the cause of mismatches 36,37 . It is in concordance with the statement from a review article by Tiercy, who mentioned that the presence of a rare HLA allele on an extended haplotype might not automatically mean that a 10/10 MUD will not be found 6 …”
Section: Discussionsupporting
confidence: 88%
“…An analysis of patients with rare HLA alleles (frequency <0.1) or HLA alleles which were not observed in our unpublished population data ( N = 10,000 from CBMDR), such as the HLA‐B*15:35, B*51:08, DRB1*11:15 , or DQB1*02:81 alleles, showed that those alleles which were part of a conserved HLA‐A~B~C~DRB1 haplotype were not the cause of mismatches 36,37 . It is in concordance with the statement from a review article by Tiercy, who mentioned that the presence of a rare HLA allele on an extended haplotype might not automatically mean that a 10/10 MUD will not be found 6 …”
Section: Discussionsupporting
confidence: 88%
“…As shown in Figure 4, the experimental comparison between the Comb-RichModel steganographic analysis model based on diversity features and other steganographic analysis algorithms, it can be seen that filtering is replaced and SPAM features are added. Compared with numerical analysis, the detection accuracy of the Comb-RichModel with diversified features has been improved to some extent, and its detection performance has improved stably from low embedding rate to high embedding rate [22][23]. Mathematical analysis is a steganographic analysis method with diverse features and high dimension.…”
Section: Resultsmentioning
confidence: 99%